Open-Top Transparent TiO2 Nanotubes Photoanodes from Evaporated Ti Layers on Fluorine-Doped Tin Oxide - Hwang, Imgon; Schmuki, Patrik; Mazare, Anca Valentina (physica status solidi (a), 2024)
Herein, the growth of transparent TiO2 nanotube (NT) layers is investigated by complete self-organized anodization of a metallic Ti layer on fluorine-doped tin oxide glass, deposited by electron beam evaporation. An initiation-free open-top tube morphology can be obtained for such transparent TiO2 NTs using an optimized second anodization approach combined with a post-ultrasonication process. The photoelectrochemical properties of open-top tubes exhibit notable enhancement, primarily attributed to their rapid electron-transfer kinetics, with a ≈33% increase in the incident-photon-to-electron conversion efficiency value (at 350 nm wavelength) in comparison to classical (initiation-covered) NTs with a comparable morphology.
CRIS-Team Scopus Importer:2024-07-19
Keywords: anodizations; electron-transport times; initiation-free; photoelectrochemistry; transparent TiO